The Neural Signature of Statistical Learning of Orthography - Tong, Xiuhong; Wang, Yi; Tong, Shelley Xiuli (Frontiers in Human Neuroscience, 2020)
While an increasing number of behavioral studies suggest the importance of statistical learning in acquiring orthographic regularity across scripts, no direct neural evidence supports this claim. The present study used event-related potentials (ERPs) to investigate the time course and the neural correlate of statistical learning of positional consistency in Chinese orthography. Visual ERPs were recorded while Chinese adults performed an orthographic statistical learning task involving artificial characters varying in high, moderate, and low levels of positional consistency. The negative ERP deflection at the N1 time window, typically linked with orthographic regularity processing, was found in orthographic statistical learning with the low and moderate consistencies eliciting larger neural responses than the high consistency in the time window of 180-240 ms over occipital-temporal brain areas. These results suggest that orthographic statistical learning begins within the first 240 ms and that the N1 might be its neural indicator.